Technology Readiness Level of biodiversity monitoring with molecular methods – where are we on the road to routine implementation? - Tiina Laamanen; Veera Norros; Petteri Vihervaara; Jacqueline Jerney; Pirkko Kortelainen; Katharina Kujala; Stefan Lambert; Janne Mäyrä; Lilja Nikula; Ida Palmroos; Mikko Tolkkinen; Kristiina Vuorio; et al. (Metabarcoding and Metagenomics)
Human activities are causing rapid biodiversity loss across ecosystems, affecting human well-being and crucial ecosystem services. Traditional biodiversity monitoring tools cannot keep up with the increasing demands of monitoring due to their limited spatial or temporal coverage, high costs, and lack of taxonomic expertise. Thus, implementation of novel molecular monitoring methods such as environmental DNA (eDNA) and DNA metabarcoding, are necessary. Molecular monitoring methods offer significant benefits for biodiversity monitoring and environmental assessment: high sensitivity and accuracy, non-invasive sampling, broad taxonomic range and cost and time efficiency. However, the diverse methodological approaches lead to poor comparability between studies and surveys, highlighting the need for standardised assessments. We used the Technology Readiness Level (TRL) framework to evaluate the maturity of molecular monitoring methods, providing a structured assessment of their readiness for routine use. In a systematic literature review, 420 articles fulfilling the study criteria were assessed and both individual studies and method categories ranked according to the TRL scale. The findings revealed a growing number of studies, particularly in aquatic environments, with most studies validating molecular technologies on a small scale but lacking large-scale system demonstrations. Aquatic eDNA-based methods targeting fish showed overall higher technology readiness compared to other sample types and taxa and applications of molecular monitoring methods ranked into the highest TRL were predominantly freshwater studies. Key barriers to the broader implementation of molecular methods to monitoring include the need for international standards, better quantitative estimates and comprehensive reference libraries. National and international cooperation is crucial for establishing common standards, ensuring reliable and comparable results and expediting the routine use of molecular methods in biodiversity monitoring. Recent efforts towards international standardisation are encouraging, but further coordinated actions are necessary for the global implementation and acceptance of these methods.